A hepatic adrenal rest tumor with a benign gallbladder tumor: a case report and literature review - Wang, Yu Chen; Li, Jiang (Frontiers in Oncology, 2025)
RationaleA hepatic adrenal rest tumor is an exceedingly rare disorder. Up to now, merely 13 cases of hepatic adrenal rest tumor have been documented in the English-language literature. Notably, the concurrent occurrence of a hepatic adrenal rest tumor and a benign gallbladder tumor in the same individual has not been previously reported. In this report, we present a case of a patient with a hepatic adrenal rest tumor who had a history of hepatitis B and was diagnosed with a benign gallbladder tumor. The tumors were successfully surgically resected, and the patient had a favorable prognosis during the follow-up period.Patient concernsWe report a 55-year-old male patient presenting with right upper abdominal discomfort, accompanied by chills and fever. He had a history of hepatitis B for more than 20 years but had not received regular medical evaluation and treatment. Serum tumor markers, including alpha-fetoprotein (AFP) and carcinoembryonic antigen (CEA), were within normal ranges. However, imaging studies showed a space-occupying lesion in the right posterior lobe of the liver and a metabolically active nodule detected by PET-CT at the base of the gallbladder.DiagnosesBased on the patient’s past medical history and imaging findings, the preoperative diagnosis was hepatocellular carcinoma and gallbladder malignancy.OutcomesThe patient underwent atypical limited hepatectomy, radical cholecystectomy for gallbladder cancer, and resection of a right adrenal tumor.ConclusionsThe histological report showed that the yellow soft tumors located in the right posterior lobe of the liver, adjacent to the adrenal region, were predominantly composed of clear cells. These cells were arranged in a pattern reminiscent of adrenal cortical tissue. Furthermore, immunohistochemistry showed that AFP (-), hepatocyte (-), melanoma antigen (MelanA) (+), inhibin-a (+), vimentin (+), synaptophysin (partially weak +), and chromogranin A (CgA) (-). The patient tolerated the surgery well, recovered uneventfully, and was discharged 11 days after surgery. There was no recurrence on follow-up.